Reforming senates in the post-revolutionary North Atlantic world:an introduction - Verstegen, S.W.; Bijleveld, Nikolaj (Routledge, 2019)
The introduction shows that the establishment and the reform of these upper legislative houses have followed remarkably parallel trajectories. Senate reforms emerged in the wake of deep political crises within the North Atlantic world and were influenced by the comparatively weak positions of small powers. Reformers responded to crises and constantly looked beyond borders and oceans for inspiration to keep their senates relevant.